The Kisaran Mengaji Movement Among Salafi Congregations: Between Religious Tradition and Modernity - Rizky Kurniawan; Rholand Muary (Jurnal Studi Agama, 2025)
The socio-cultural friction experienced by Salafi women often leads to misconceptions about Salafi concepts. This study aims to determine how Salafi women view religious traditions and how they adapt their religious activities to the tide of modernity. This study uses a case study approach with qualitative research. Data collection techniques were carried out through non-participant observation and in-depth interviews. The results show that 1) Salafi women in the Kisaran Mengaji Movement view local religious traditions through a strict categorization between practices that are considered in accordance with the Sunnah and practices that are considered bid'ah, there is a negotiation between Salafi manhaj commitment and social harmony, participation in the Mengaji Movement contributes to the formation of the religious identity of Salafi female congregants, and the dynamics of the relationship between Salafi female congregants and the social environment that still strongly holds on to local traditions; 2) Salafi women in the Kisaran Mengaji Movement adapt religious activities to the tide of modernity by utilizing digital technology to strengthen religious practices, negotiating time between domestic demands, work, and studies, forming a religious-modern lifestyle in public spaces and the world of work, parenting, digital literacy, and control over the tide of modernity